PENGARUH TRUSTWORTHINESS, EXPERTISE DAN ATTRACTIVENESS CELEBRITY ENDORSER DI INSTAGRAM TERHADAP PURCHASE INTENTION PRODUK HIJAB (Studi Kasus pada Akun Instagram @gitasav) - Syarifah Fatimah Dina Najib H.A; Islahuddin Daud; Aslamia Rosa (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2019)
This study was aimed to examine the effects of trustworthiness, expertise, and attractiveness of celebrity endorser on Instagram to purchase intention of hijab products. The sampling technique was done by purposive sampling method. The population in this study was followers of the @gitasav Instagram account. Data was collected through distributing questionnaires to 100 respondents. The analysis technique used in this study is multiple linear regression analysis. The results showed that simultaneously the variables of trustworthiness, expertise, and attractiveness had a significant effect on purchase intention. However, partially the purchase intention variable is only influenced by the trustworthiness variable which is equal to 3,878. In this study a regression model was obtained, which is Y = 10,021 + 0,655X1 + 0,038X2 - 0,122X3.